Investigação de doenças neurológicas em equinos testados negativados para raiva (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2011)
There are several central nervous system (CNS) diseases that can infect horses, and the differential diagnoses are therefore necessary. Clinically these diagnoses are often difficult once the degrees of ataxia and paresis are similar. The most commonly encountered abnormalities that may result in neurological dysfunction include trauma, equine herpesvirus, Eastern, Western and Venezuelan equine encephalomyelitis (EEE, WEE, VEE), leukoencephalomalacia, protozoan myeloencephalitis and bacterial encephalitis. The aimof this work was to identify the main diseases with neurological signs in equine after negative diagnosis for rabies. From April 2007 to June 2011, 167 samples of CNS rom animals that have died with neurological signs were submitted for rabies diagnosis by FAT (fluorescent antibody test) and MIT (mouse inoculation test). Those tested negative were further submitted to other analysis. Samples of the CNS were inoculated in cell culture and submitted to PCR for detection of herpesvirus and equine encephalomyelitis. In order to investigate the growth of bacteria, isolation in 5% blood agar and biochemical identification was performed. For the histological examination, CNS tissue samples were placed in 10% neutral buffered formalin and embedded in paraffin, sectioned and stained with hematoxylin eosin. Our data confirmed rabies in 23 (13.8%) cases. Of 144 samples tested negative for rabies, 10 (7.0%) were positive for leukoencephalomalacia, 4 (2.8%) for herpetic myeloencephalitis and 12 (8.3%) for bacterial encephalitis. This study highlights the importance of including different diagnosis in samples from equine with neurological disease.